Correlation of ApoE Gene Polymorphism with Coronary Heart Disease Severity in Patients with Acute Coronary Syndrome Who Receive Statin Therapy, Padang, Indonesia - Elly Usman; Gestina Aliska; Masrul Syafri (Universitas Andalas, 2022)
Coronary Heart Disease (CHD) is still the most common cause of death. Ischemic heart disease causes more than 7 million (12.8%) deaths worldwide. It is estimated that 3,750,000 Indonesians have CHD. CHD is a disease with many risk factors. ApoE gene polymorphism is associated with atherosclerosis and plays a role in lipid metabolism, which is 2-16% affecting variability in LDL levels. This study aims to look at the relationship between ApoE gene polymorphism and the severity of coronary heart disease. Data regarding ApoE gene polymorphism was obtained using polymerase chain reaction (PCR). DNA was isolated from white blood cells using DNA purification kit. ApoE2, ApoE3, ApoE4 alleles were detected by DNA sequencing. Data on the severity of coronary heart disease were obtained from angiography and were calculated based on SYNTAX scores. In this study, ApoE was obtained with e2 allele frequencies (4.63%), e3 (78.70%), and e4 (16.67%) with E2 / 2 (0%), E2 / 3 (3.70%), E2 / 4 (5.56%), E3 / 3 (64.81%), E3 / 4 (24.07%), and E4 / 4 (1.85%). The relationship between the SYNTAX score and the ApoE genotype has no significant difference. ApoE3 / 4 genotype has the highest SYNTAX score and the e4 allele has the most influence on CHD despite the influence of statin therapy.